Brief intervention medication therapy management: Establishment of an opioid misuse intervention model delivered in a community pharmacy. (2nd January 2021) - Kenney, Amy; Cox, Nicholas; Bryan, M Aryana; Cochran, Gerald
Abstract: Purpose: Medication expertise and close patient contact position community pharmacists to make significant contributions to combatting the opioid epidemic. This position facilitated the development and initial implementation of the Brief Intervention Medication Therapy Management (BIMTM) model to detect and address patient opioid misuse. BIMTM is an intervention consisting of 9 sessions. One medication management session is delivered by a pharmacist in a community pharmacy setting, and the remaining sessions are delivered telephonically by a patient navigator to follow up with goals established with the pharmacist and address concomitant health concerns that increase risk for misuse. Methods: We employed the Consolidated Framework for Implementation Research (CFIR) to summarize and present key findings from 4 distinct studies. CFIR domains addressed were (1) intervention characteristics, (2) outer setting, (3) inner setting, (4) process, and (5) characteristics of individuals. The study results show sequential development of evidence for BIMTM. Results: A multistate cross-sectional pharmacist survey ( n = 739) demonstrated limited pharmacist training and/or resources to address misuse, suggesting the need for external intervention development. Our multistakeholder intervention planning project showed limitations of current evidence-based models of care and of intervention implementation, which resulted in construction of the BIMTM. A multisite cross-sectional screening survey of patients ( n = 333) established an electronic misuse screening protocol within 4 community pharmacies and identified opioid misuse in 15% of screened patients; among those patients, 98% had concomitant health conditions that contribute to the risk of opioid misuse. Presentation of study results to pharmacy leaders produced commitment for intervention implementation and a partnership to develop a grant proposal supporting this action. Our small-scale randomized trial evinced success in recruitment and retention and BIMTM patient benefit. The small-scale randomized trial likewise showed high levels of satisfaction with BIMTM. Conclusion: The establishment of BIMTM supports community pharmacist identification and intervention with patients engaged in misuse. Continued use of this research-based strategy may further empower pharmacists to address the opioid epidemic.